Late Pleistocene to late Holocene palaeoecology and human foraging at Kuumbi Cave, Zanzibar Island - Iminjili, Victor; Stewart, Mathew; Culley, Courtney; Hixon, Sean; Goldstein, Steve; Bleasdale, Madeleine; Jesús Sanchez Flores, Antonio; Lucas, Mary; Ilgner, Jana; Prendergast, Mary E.; Crowther, Alison; Boivin, Nicole; et al. (Frontiers in Environmental Archaeology, 2023)
Background Climate change played a major role in shaping regional human-environment interactions in Africa during the late Pleistocene-Holocene, but this topic has not been exhaustively studied, particularly in eastern Africa. While there is growing evidence that the coastal and island settings in this region played a critical role in human evolution, combined archaeological and palaeoenvironmental studies have tended to focus on the arid interior and show the dominance of grasslands with patches of closed and open woodlands during the last 20,000 years. Methods Here, we present stable carbon and oxygen isotope analyses of zooarchaeological remains (n = 229) recovered from Kuumbi Cave, Zanzibar Island, spanning the last glacial period and the Holocene (20,000 to 500 cal. BP). Results Our data demonstrate that the vicinity of Kuumbi Cave was consistently covered by mosaic habitats, dominated by forests and small patches of open woodland and grassland. The inhabitants of Kuumbi Cave exploited these diverse tropical habitats even after the regional arrival of agriculture. Discussion We suggest that the stable coastal forest mosaic habitats acted as a refugium for foragers during glacial periods and that the Iron Age inhabitants of Kuumbi Cave were not food producers migrating from the interior, but rather Indigenous foragers interacting with food production.